Osteomyelitis caused by Aspergillus species: a review of 310 reported cases. (15th October 2013) - Gabrielli, E.; Fothergill, A. W.; Brescini, L.; Sutton, D. A.; Marchionni, E.; Orsetti, E.; Staffolani, S.; Castelli, P.; Gesuita, R.; Barchiesi, F.; Roilides, E.
Abstract Aspergillus osteomyelitis is a rare infection. We reviewed 310 individual cases reported in the literature from 1936 to 2013. The median age of patients was 43 years (range, 0–86 years), and 59% were males. Comorbidities associated with this infection included chronic granulomatous disease (19%), haematological malignancies (11%), transplantation (11%), diabetes (6%), pulmonary disease (4%), steroid therapy (4%), and human immunodeficiency virus infection (4%). Sites of infection included the spine (49%), base of the skull, paranasal sinuses and jaw (18%), ribs (9%), long bones (9%), sternum (5%), and chest wall (4%). The most common infecting species were Aspergillus fumigatus (55%), Aspergillus flavus (12%), and Aspergillus nidulans (7%). Sixty‐two per cent of the individual cases were treated with a combination of an antifungal regimen and surgery. Amphotericin B was the antifungal drug most commonly used, followed by itraconazole and voriconazole. Several combination or sequential therapies were also used experimentally. The overall crude mortality rate was 25%.